2020
DOI: 10.36108/laujoces/0202/40(0150)
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Assessment of Effects of Encroachment on Water Resources of Agba Dam, Ilorin Nigeria

Abstract: The city of Ilorin in Nigeria has experienced high population growth and rapid urbanization. Agba Dam is one of the major sources of potable water in Ilorin, and currently being threatened by anthropogenic induced encroachment activities, with potential for significant derogatory effects on its quality. Therefore, this paper assesses the qualitative impact of encroachment on the water resources regime of Agba Dam, Ilorin, Nigeria. Field survey was carried out to scope proximal anthropogenic activities and to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The siltation problem in Agba reservoir is discussed in relation to some of the physicochemical and biotic properties of the reservoir, which facilitated its functioning for drinking water supply, artisanal fisheries and tourism and not as an engineering problem. Busari et al (2014) and Oladeji et al (2016) had earlier reported the average siltation rate and reduction in the reservoir storage volume capacity and buffer boundary. Their results are corroborated by the significant reduction in depth at the bed of the reservoir from the original 17.8 m in 1952 to 12.9 m in 2015 recorded in this study.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The siltation problem in Agba reservoir is discussed in relation to some of the physicochemical and biotic properties of the reservoir, which facilitated its functioning for drinking water supply, artisanal fisheries and tourism and not as an engineering problem. Busari et al (2014) and Oladeji et al (2016) had earlier reported the average siltation rate and reduction in the reservoir storage volume capacity and buffer boundary. Their results are corroborated by the significant reduction in depth at the bed of the reservoir from the original 17.8 m in 1952 to 12.9 m in 2015 recorded in this study.…”
Section: Discussionmentioning
confidence: 95%
“…Busari et al (2014) reported the siltation in Agba reservoir, Ilorin, Nigeria, and that the average siltation rate of the reservoir is 9180 m 3 /year, resulting in the lake losing 41.67% of its original capacity in its 68‐year history. Similarly, Oladeji et al (2016) noted that a significant reduction of 63% in the historical buffer boundary of the reservoir, which suggests potential impact on the catchment and consequently on the quality of the lake water resources, while Abdus‐Salam et al (2016) reported the sediments of the reservoir showed a large percentage of some metals occurring in the non‐bioavailable and bioavailable fractions, of which the bioavailable fractions could be a source of problem to the reservoir if leached to the water body when the right pH in the reservoir is attained thereby disrupting the limnology and functioning of the reservoir.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation